2019
DOI: 10.1103/physrevmaterials.3.074402
|View full text |Cite
|
Sign up to set email alerts
|

Spin generation in completely MBE-grown Co2FeSi/MgO/GaAs lateral spin valves

Abstract: We demonstrate first measurements of successful spin generation in crystalline Co 2 FeSi/MgO/GaAs hybrid structures grown by molecular-beam epitaxy (MBE), with different MgO interlayer thicknesses. Using non-local spin valve and non-local Hanle measurement configurations, we determine spin lifetimes of τ ≈ 100 ns and spin diffusion lengths of λ ≈ 5.6 µm for different MgO layer thicknesses proving the high quality of the GaAs transport channel. For an optimized MgO layer thickness, the bias dependence of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Mitigation of this effect is an ongoing effort. Further, although there has been some exploration of using non-ferromagnetic materials for spintronic applications [52], this research avenue is still nascent, especially in context of spin injection utilizing Heusler compounds [53][54][55][56][57]. This motivates further study of interfaces between semiconductors and lattice matched Heusler compounds, especially those with high Fermi-level spin polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation of this effect is an ongoing effort. Further, although there has been some exploration of using non-ferromagnetic materials for spintronic applications [52], this research avenue is still nascent, especially in context of spin injection utilizing Heusler compounds [53][54][55][56][57]. This motivates further study of interfaces between semiconductors and lattice matched Heusler compounds, especially those with high Fermi-level spin polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Using a general X 2 YZ chemical formula, where X and Y denote transition metals while Z denotes one of the main-group elements, most of half-metallic alloys belong to wide Co 2 YZ group 4 , 12 with half-metallicity and high Curie temperature 4 , 13 . Co 2 YZ Heusler alloys are widely used in various spintronic applications, like tunnel magnetoresistance devices 14 , 15 , current-perpendicular-to-plane giant magnetoresistance devices 16 28 , lateral spin-valves 29 31 and spin injectors into semiconductors 9 , 32 , 33 . The last studies also revealed topological semimetal properties in such materials 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The last studies also revealed topological semimetal properties in such materials 34 . Up to now Co 2 YZ Heusler alloys remain among the ones of greatest research interest 6 , 10 , 31 , 34 46 .…”
Section: Introductionmentioning
confidence: 99%
“…11) Moreover, the MgO interlayer enhances the spin injection efficiency due to its spin filtering effects 3,12) and it also suppresses the diffusion of atoms between CoFeB and GaAs. 13) On the other hand, the junction resistance increases exponentially with the thickness of MgO, 14,15) which degrades device characteristics, such as magnetoresistance, transconductance, and current-drive capability. Thus, in the CoFeB/MgO system, obtaining low junction resistance may not be compatible with keeping PMA with sufficient thermal stability.…”
mentioning
confidence: 99%